The Collective Ijtihad Practice in Indonesia: The Role of Isbat Sessions in Addressing Legal Paradigm Differences Between Hisab-Rukyat - AM, Suhar; Fitra, Tasnim Rahman; Kasdi, Abdurrohman; Istiqomah, Khusnul; Abdurrahman, Abdurrahman; Ahmad, Humaira (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
This article aims to promote the Isbat session as a collective ijtihad practice that can overcome the differences in the legal paradigms of Hisab and Rukyat in determining the beginning of Ramadan in Indonesia. This study uses qualitative-descriptive analysis by observing the practice of the Isbat session in dealing with differences in the legal paradigms of Hisab-Rukyat in Indonesia. Primary data uses official documents from the Ministry of Religious Affairs regarding the Isbat Session from time to time. Then the data is elaborated with secondary data, especially the opinions of scholars regarding the role of collective ijtihad in dealing with differences in the paradigms of Islamic law. The article finds that the Isbat Session is a real example of the practice of collective ijtihad in Indonesia, which combines religious values, science, and the principle of deliberation. Its role is very significant in bringing together the diversity of paradigms and legal views of the Islamic community in Indonesia. Furthermore, the practice of the Isbat session also has an impact on the socio-community aspect in strengthening the unity of Muslims amidst the diversity of legal methods and views. This article contributes to the development of Islamic legal science to become a reference for academics on related issues.